The benefits of auditors’ sustained ethical behavior: increased trust and reduced costs - Morales-Sánchez, Rafael (Journal of business ethics, 2020)
Studies demonstrating the benefits of ethical behavior at an individual level are scarce. The business ethics literature centers its analysis on unethical behaviors and their consequences, rather than ethical behaviors and their benefits. There is now considerable debate on the role of auditors in society and the function of accounting firms in the free market capitalist system. Specifically, the eminently ethical nature of the auditor’s work has been highlighted. Therefore, the aim of our paper is to show the impact of auditors’ sustained ethical behavior: the trust it generates. This trust results in considerable benefits for the firm due to a reduction in the costs of the partner’s supervision of the auditor. The methodology chosen to validate these claims is a survey of partner of the audit firm in auditing companies. The results of this research confirm the hypotheses raised in the theoretical model.